IDENTIFICATION AND CONTROL STRATEGIES OF BOVINE VIRAL DIARRHOEA VIRUS (BVDV) - DR.M.SRINIVAS; DR.N.R.SRIKANTH (International Journal of Pharma and Bio Sciences, 2012)
Bovine viral diarrhoea virus (BVDV) is a Pestivirus in the family Flaviviridae and is closely related to classical swine fever and ovine border disease viruses. Two antigenically distinct genotypes of BVDV exist, types 1 and 2. According to the OIE (2008), bovine viral diarrhoea/mucosal disease (BVD/MD) and classical swine fever (CSF) are notifiable diseases and hence eradication programmes are underway in several countries worldwide. Scandinavian countries were extremely successful in controlling BVDV infection while limited success was achieved in U.S.A. One of the most important aspects of the disease is that, there are no pathognomonic clinical signs of infection with bovine viral diarrhoea virus (BVDV) in cattle. Diagnostic investigations therefore rely on laboratory-based detection of the virus, or of virus-induced antigens or antibodies in submitted samples. The serological evidence that BVDV infection is widespread in India is of utmost practical importance and more focus is to be concentrated in controlling the disease. The present review aims in discussing the methods of detecting the BVD virus in different samples and the strategies required to control the spread of infection.